Interference of the co-exposure of mercury with silica-coated iron oxide nanoparticles can modulate genotoxicity induced by their individual exposures-a paradox depicted in fish under in vitro conditions - Mohmood, Iram
The study aimed to assess the genotoxic potential of silica-coated iron oxide nanoparticle functionalized with dithiocarbamate groups (IONP, 100 nm) in vitro exposure alone or its interference with mercury (Hg) co-exposure in the blood of European eel (Anguilla anguilla L.) by evaluating 8-hydroxy-2'-deoxyguanosine (8-OHdG), lipid peroxidation (LPO), and erythrocytic nuclear abnormalities (ENA). Four groups were made: (i) 2 x 10(6) erythrocytes + Roswell Park Memorial Institute-1640 (RPMI-1640) (control), (ii) 2 x 10(6) erythrocytes + IONP (2.5 mg L-1), (iii) 2 x 10(6) erythrocytes + Hg (50 mu g L-1), and (iv) 2 x 10(6) erythrocytes + IONP + Hg. Blood plasma was also processed following the previous exposure conditions. Samplings were performed at 0, 2, 4, 8, 16, 24, 48, and 72 h of exposure. The results revealed significant ENA increases at both early (2, 4, 8) and late (16, 24, 48, 72) hours of exposure to IONP alone. However, IONP exposure combined with Hg co-exposure revealed no ENA increase at 2 h, suggesting that IONP-Hg complex formation is efficient to eliminate the DNA damage induced by individual exposure to IONP or Hg at early hours. Hence, the initial occurrence of antagonism between IONP and Hg was perceptible; however, at late hours of exposure, IONP was unable to mitigate the mercury-accrued negative impacts. Plasma exposure to IONP alone displayed a significant increase in 8-OHdG levels at 2 and 48 h of exposure. However, IONP in combination with Hg co-exposure revealed an increase in 8-OHdG levels at all the exposure length (except 16 h), suggesting that both IONP and Hg independently oxidized DNA. In addition, an additive effect on 8-OHdG levels at both early and late hours, and on LPO only at late hours (except 24 h), suggested that DNA is more susceptible to peroxidative damage than lipid.